The use of N-of-1 trials to generate real-world evidence for optimal treatment of individuals and populations - Harry P. Selker; Dorothy Dulko; David J. Greenblatt; Marisha Palm; Ludovic Trinquart (Journal of Clinical and Translational Science, 2023)
Abstract